Hubungan Minat Belajar dengan Hasil Belajar Matematika Peserta Didik Kelas X - Sera, Yohana Yunita Alehandra Bunge; Jagom, Yohanes Ovaritus; Orangola, Yulianus (Papanda, 2025)
This study aims to determine the relationship between learning interest and mathematics learning outcomes of grade X students at Giovanni Catholic High School in Kupang. In reality, students' mathematics learning outcomes are still low due to low learning interest, which affects their learning achievement. This study uses a quantitative approach with a correlational method. The population in this study was all tenth-grade students at Giovanni Catholic High School in Kupang, who were selected using purposive sampling. The instruments used were a learning interest questionnaire with indicators of enjoyment, attention, interest, and involvement, as well as mid-semester summative scores (STS) in mathematics as learning outcome data. Data analysis was performed using the Shapiro–Wilk normality test and Spearman's rho correlation test with the help of SPSS Statistics 26. The results showed a positive and significant relationship between learning interest and students' mathematics learning outcomes. This means that the higher the students' learning interest, the higher the learning outcomes achieved. These findings are expected to serve as a basis for educators in designing more interesting and participatory learning strategies to increase interest and learning outcomes in mathematics.